2022
DOI: 10.1101/2022.11.02.514978
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of NAD-RNAs and ADPR-RNA decapping in the archaeal model organismsSulfolobus acidocaldariusandHaloferax volcanii

Abstract: NAD is a coenzyme central to metabolism that was also found to serve as a 5′-terminal cap of bacterial and eukaryotic RNA species. The presence and functionality of NAD-capped RNAs (NAD-RNAs) in the archaeal domain remain to be characterized in detail. Here, by combining LC-MS and NAD captureSeq methodology, we quantified the total levels of NAD-RNAs and determined the identity of NAD-RNAs in the two model Archaea,Sulfolobus acidocaldariusandHaloferax volcanii. A complementary differential RNA-Seq (dRNA-Seq) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…1b). RNAs harbouring a 5’-NAD-cap were recently found in bacteria, including E. coli 3,10,11 , archaea 12,13 , and higher organisms 5,1419 , where NAD-RNA concentrations range from 1.9 to 7.4 fmol/μg RNA 16 . The modification was observed in different RNA types, including messenger RNAs (mRNAs) and small regulatory RNAs (sRNAs) 20 .…”
mentioning
confidence: 99%
“…1b). RNAs harbouring a 5’-NAD-cap were recently found in bacteria, including E. coli 3,10,11 , archaea 12,13 , and higher organisms 5,1419 , where NAD-RNA concentrations range from 1.9 to 7.4 fmol/μg RNA 16 . The modification was observed in different RNA types, including messenger RNAs (mRNAs) and small regulatory RNAs (sRNAs) 20 .…”
mentioning
confidence: 99%
“…In eukaryotes, various Nudix hydrolases (termed "NudT") capable of removing different caps from RNA in vitro have been identified (Abdelraheim et al, 2003;Song et al, 2010Song et al, , 2013Grudzien-Nogalska et al, 2019). NAD-capped RNA has been identified in bacteria and eukaryotes and recently also in the archaeal domain in Sulfolobus acidocaldarius and Haloferax volcanii (Chen et al, 2009;Cahová et al, 2015;Jiao et al, 2017;Walters et al, 2017;Ruiz-Larrabeiti et al, 2021;Gomes-Filho et al, 2022). Furthermore, methylated and non-methylated dinucleoside polyphosphates (Np n Ns) were identified at the 5′ ends of E. coli RNA (Hudeček et al, 2020) and most recently, ADPR-capped RNA was identified in human cells (Weixler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In eukaryotes, various Nudix hydrolases (termed "NudT") capable of removing different caps from RNA in vitro have been identified (Abdelraheim et al, 2003;Song et al, 2010Song et al, , 2013Grudzien-Nogalska et al, 2019). NAD-capped RNA has been identified in bacteria and eukaryotes and recently also in the archaeal domain in Sulfolobus acidocaldarius and Haloferax volcanii (Chen et al, 2009;Cahová et al, 2015;Jiao et al, 2017;Walters et al, 2017;Ruiz-Larrabeiti et al, 2021;Gomes-Filho et al, 2022). Furthermore, methylated and non-methylated dinucleoside polyphosphates (Np n Ns) were identified at the 5′ ends of E. coli RNA (Hudeček et al, 2020) and most recently, ADPR-capped RNA was identified in human cells (Weixler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The Nudix family is known for displaying a large substrate range, especially in vitro, encompassing canonical and oxidized nucleotides, nucleotide sugars, dinucleotide coenzymes, diadenosine polyphosphates and capped RNAs, as well as non-nucleotide substrates such as inositol pyrophosphates (McLennan, 2013;Srouji et al, 2017). While the Nudix protein Saci_ NudT5 demonstrated ADPR-RNA decapping ability in vitro, the other proteins' activities remain elusive (Gomes-Filho et al, 2022). To this end, this study presents the impact of Nudix hydrolase absence on the transcriptome of S. acidocaldarius.…”
Section: Introductionmentioning
confidence: 99%